Association between alcohol consumption, marijuana use and road traffic injuries among commercial motorcycle riders: A population-based, case-control study in Dares Salaam, Tanzania. (September 2021) - Kiwango, George; Francis, Filbert; Moshiro, Candida; Möller, Jette; Hasselberg, Marie
Highlights: A case-control study was used to investigate alcohol consumption and marijuana use among commercial motorcycle riders. Effects of alcohol consumption and marijuana use on risk of RTIs was adjusted for potential confounders. Risky driving behaviours are potential confounders of the risk of RTIs among commercial motorcycle riders. Broaden the understanding of influence of alcohol and marijuana use on RTIs among commercial motorcycle riders in sub-Saharan Africa. Abstract: Background: Alcohol consumption and psychoactive drug use are well-recognised risk factors for road traffic injuries (RTIs). Both types of use may impair and affect drivers' performance. Yet, there is limited literature on their contribution to RTIs among commercial motorcycle riders, particularly in low- and middle-income settings. This study aimed to determine the association between alcohol consumption, marijuana use and RTIs among commercial motorcycle riders in the city of Dar es Salaam, Tanzania. Methods: We conducted a case-control study between July 2018 and March 2019. Cases (n = 164) were commercial motorcycle riders who had sustained an RTIs and attended at a hospital. Controls (n = 400) were commercial motorcycle riders who had not experienced an RTIs that led to hospital attendance during the past six months. Alcohol consumption was assessed using the Alcohol Use Disorder Identification (AUDIT) score, which classified participants as a non-drinker, normal drinker(1–7 scores) and risky drinker (scores ≥ 8). Marijuana use was assessed through self-reported use in the past year. We estimated odds ratios (ORs) using logistic regression adjusted for sociodemographic, driver-, and work-related factors. Results: Risky drinking was associated with close to six times the odds of RTIs compared to non-drinkers (OR = 5.98, 95% CI: 3.25 – 11.0). The association remained significant even after adjusting for sociodemographic, driving and work-related factors (OR = 2.41, 95% CI: 1.01 – 5.76). The crude odds ratios of RTIs were significantly higher among users of marijuana than non-users (OR = 2.33, 95% CI: 1.38 – 3.95). However, the association did not remain statistically significant after adjusting for confounders (OR = 1.11, 95% CI = 0.49–2.48). Conclusion: Our findings confirm increased odds of RTIs among commercial motorcycle riders with risky drinking behaviour even after taking sociodemographic, driving and work-related factors into account. Unlike alcohol consumption the relationship between marijuana use and RTIs among commercial motorcycle riders was unclear. Since motorcycle riders are more susceptible to the effect of alcohol due to higher demands of balance and coordination and because commercial motorcyclist riders, in particular, they spend a considerable amount of time on the road, our results underscore the importance of addressing hazardous alcohol consumption and marijuana use in future prevention strategies to enhance road safety.